Identifying bottlenecks and designing ideas and solutions for improving aircraft passengers' experience during boarding and disembarking. (May 2019) - Hiemstra-Van Mastrigt, Suzanne; Ottens, Richard; Vink, Peter
Abstract: Interferences during the boarding procedure are one of the main reasons of delay and increased turnaround time, becoming a relevant problem for airlines. Observations of the boarding process and questionnaires inside the aircraft revealed three main bottlenecks during the boarding process: (1) Hand luggage: Storage space is not sufficient and/or not used efficiently; (2) Preparation: Passengers are not well prepared for the boarding process; and (3) Communication: Audio announcements are unclear and unfocused. By translating these bottlenecks as possibilities for improvement, solutions were designed for the airport and aircraft interiors to reduce boarding time and improve the passenger boarding experience. Concepts ranged from an app to scan your hand luggage at home and make a reservation for overhead bin space; to a redesigned waiting area to help passengers prepare for boarding; to new boarding methods and redesigned aircraft seats. In this paper, several design concepts are presented in more detail. Highlights: Observational research on actual passenger behaviour during aircraft boarding. Three main bottlenecks are: hand luggage, lack of preparation (by pax), communication. Bottlenecks were translated into design solutions to improve boarding experience. Design opportunities seem possible, besides experimenting with boarding strategies. Solutions for providing a faster and more comfortable boarding process.